ANALISIS ACTIVITY BASED COSTING UNTUK MENENTUKAN HARGA POKOK PRODUKSI PADA MENARA ASRI BAKERY KOTA PROBOLINGGO - Titin Krisnawati; Khusnik Hudzafidah; Samsul Ma’arip Fussoleh (Gapenas Publisher, 2022)
This research based on the formulation and purpose of the study on the tower scenic bakery in probolinggo for the purpose of analyzing the determination of the base price of production based on a method of activity based costing. The kind of research in this using quantitative descriptive according to the primary data and skunder. Variables used in it is composed activity based costing and the base price. Production. The data used in the analysis if data is primary data from the report production costs for years 2018 which includes data, raw material costs labor, and overhead cost as the object of research. Data collection techniques consisting of interview , observation and as well as documentation, Based on analysis techniques the data used in the cost of goods through the method of production based on abc or activity based costing, It further analyzes the results obtained from the production of torn bread with the ABC method. Based on the results of research analysis can be concluded that the calculation of hpp or the cost of production with the ABC method on the production of torn bread in the bakery salty tower at a rate per unit of production of Rp.3,965.6 per unit after the burden of production activity costs